2022
DOI: 10.3389/fendo.2022.873012
|View full text |Cite
|
Sign up to set email alerts
|

FURIN Promoter Methylation Predicts the Risk of Incident Diabetes: A Prospective Analysis in the Gusu Cohort

Abstract: BackgroundFurin has been associated with diabetes but the underlying mechanisms are unclear. As a mediator linking fixed genome and dynamic environment, DNA methylation of its coding gene FURIN may be involved. Here, we aimed to examine the prospective association between DNA methylation in FURIN promoter and incident diabetes during 4 years of follow-up in Chinese adults.MethodsDNA methylation levels in FURIN promoter were quantified by target bisulfite sequencing using peripheral blood from 1836 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Such discrepancies need to be taken into consideration and additional research needs to be performed on individuals with different ethnicities and backgrounds. In a different study using the same population, He and colleagues suggested an association between the hypermethylation of the FURIN promoter, which mostly predicts lower furin protein levels and an increased risk of diabetes incidence [52]. As the study mentioned earlier, reduced serum furin levels were also negatively associated with an increased risk of obesity and hypertension which share many risk factors and molecular mechanisms with diabetes [53,54].…”
Section: The Association Of Furin Levels With Diabetes and Mortalitymentioning
confidence: 91%
“…Such discrepancies need to be taken into consideration and additional research needs to be performed on individuals with different ethnicities and backgrounds. In a different study using the same population, He and colleagues suggested an association between the hypermethylation of the FURIN promoter, which mostly predicts lower furin protein levels and an increased risk of diabetes incidence [52]. As the study mentioned earlier, reduced serum furin levels were also negatively associated with an increased risk of obesity and hypertension which share many risk factors and molecular mechanisms with diabetes [53,54].…”
Section: The Association Of Furin Levels With Diabetes and Mortalitymentioning
confidence: 91%
“…65 Similarly to what is seen in hypertension, a study with 4 years of follow up found that nondiabetic individuals with DNA hypermethylation of the promoter region of the FURIN gene might have an increased risk of diabetes (Table 2). 66 Pancreatic β cell dysfunction and insulin resistance might occur if furin is downregulated. Furin is highly expressed in pancreatic islets.…”
Section: ■ Diabetes Mellitusmentioning
confidence: 99%